1995
DOI: 10.1109/77.402882
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the oxygenation process in the critical currents of bulk melt textured YBa/sub 2/Cu/sub 3/O/sub 7/

Abstract: Bulk superconductingYBa2CugO7-Y2BaCu05 composites have been prepared through a directional solidiJcation process allowing to obtain quasi-single crystals up to 10-12 cm in length with critical currents well above lo5 A/cm2 at 77 K and zero field. Low temperature oxygenation processes have been required to reach the optimal superconducting performances of the samples. For short oxygenation times, oxygen deficient bands parallel to the a-b planes have been observed while, on the other hand, an aging process has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1997
1997

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…We have shown that in melt-textured 123-211 composites dark bands, typically 50-100 µm wide, develop parallel to the ab planes and their width is controlled by the duration of the oxygenation process [115,116]. Low-field zero-field cooling (ZFC) measurements allow us to identify these dark bands with oxygen-deficient areas (see figure 8), since in the H ab geometry full shielding is reached only when supercurrents cross these poorly oxygenated zones.…”
Section: Oxygenation Effectsmentioning
confidence: 97%
“…We have shown that in melt-textured 123-211 composites dark bands, typically 50-100 µm wide, develop parallel to the ab planes and their width is controlled by the duration of the oxygenation process [115,116]. Low-field zero-field cooling (ZFC) measurements allow us to identify these dark bands with oxygen-deficient areas (see figure 8), since in the H ab geometry full shielding is reached only when supercurrents cross these poorly oxygenated zones.…”
Section: Oxygenation Effectsmentioning
confidence: 97%